(3CHjGJ TYQjIs - (3Ydj Hf CHj WGdH GdbQTj,J (B40 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HGQi GdNdb hGdUhQ hHGSW GdQRb ddCfYGe hGdHTQ hcd Ndb jQGg agh jQRbg Yfg JYGdi Zfi ZjQ eaJbQ s
(3BNQgG (B:s
(3gPG hUdi Edg GdYGdejf Ydi eMeO NjQ eHYhK ef GdHTQ hGdGd hGdUMH Ke GdJGHYjf dge hJGHYjge ef GdBUGd hGdHcQ JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3jdi GdeNWhW ahGFO dehdGfG TgGH GdOjf GdeUQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9270) s
Keywords: (3GdCOHs